Pengamanan Sarana dan Prasarana di SDN Mangli 01 Jember - Moelyaning Siwi; Muhammad 'Ainul Yaqin; M Goris Hoirul M; Khoirul Anam; Rofiq Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
Facilities and infrastructure are an important part of supporting the creation of a safe, comfortable learning environment, and supporting an optimal learning process. Therefore, the security of physical assets in schools needs to be managed in a planned and sustainable manner. This study examines the definition, legal basis, theoretical steps, as well as the results of observations and real obstacles in the field. Through preventive and repressive approaches, security is carried out in three stages: planning, implementation, and evaluation. The observation results showed that although the school had implemented several preventive measures such as the installation of CCTV and the locking of spaces, there were no permanent security officers available, and supervision was limited to operating hours. The lack of a physical security system is a major challenge. Therefore, improving security infrastructure and the involvement of all school residents is key in creating a safe and sustainable learning environment. This study is expected to be a reflection and inspiration in managing educational assets strategically and responsibly.